IS SERUM ZINC LEVEL CORRELATED WITH INSULIN RESISTANCE AMONG LACTATING MOTHERS IN JAKARTA? - Dian Araminta Ramadhania; Diana Sunardi; Ali Sungkar (World Nutrition Journal, 2020)
Introduction: Insulin resistance is a condition that underlies the development of diabetes mellitus. The prevalence of diabetes mellitus keeps rising, including in Indonesia. A higher proportion of diabetes was found in women. Physiological changes during pregnancy can cause insulin resistance that may persist until postpartum period. Lactation and nutrient like zinc may improve insulin resistance. This study aimed to measure the correlation between zinc serum level and insulin resistance of lactating mothers in Jakarta.Methods: This study used cross-sectional design, was conducted in Puskesmas Kecamatan Grogol Petamburan, West Jakarta and Puskesmas Kecamatan Cilincing, North Jakarta from February to April 2019. A total of 75 lactating mothers at 3–6 months postpartum were selected using consecutive sampling method. Zinc serum was analyzed using atomic absorption spectrophotometry (AAS) method. Insulin resistance was assessed using the homeostasis model assessment-insulin resistance (HOMA-IR).Results: Approximately 76% (n = 57) subjects had low serum zinc level. Spearman correlation test between serum zinc level and HOMA-IR was done (r = 0.003, p = 0.977). Also, correlation test between BMI and HOMA-IR (r = 0.563, p <0.001).Conclusion: No correlation was found between serum zinc level and HOMA-IR however, there was a significant moderate positive correlation between BMI and HOMA-IR.Keywords: Lactation, zinc, insulin resistance, HOMA-IR, BMI